Nilai Religius dalam Novel Bulan Terbelah di Langit Amerika Karya Hanum Salsabiela Rais dan Rangga Almahendra: Tinjauan Semiotika dan Implementasinya Sebagaibahan Ajar Sastra di SMK Muhammadiyah Kartasura - Sari, Candra Wulan; , Drs. Adyana Sunanda, M.Pd (2017)
The purpose of this study is to describe, (1) structures that build up a novel Bulan Terbelah di Langit Amerika by Hanum Salsabiela Rais dan Rangga Almahendra, (2) the religious that contained in Bulan Terbelah di Langit Amerika by Hanum Salsabiela Rais dan Rangga Almahendra, (3) the implementation of the research in the novel Bulan Terbelah di Langit Amerika by Hanum SalsabielaRais dan Rangga Almahendra. This research used qualitative descriptive methods. The object of this research is the word and sentences which containing a message of religious values in the BulanTerbelah di Langit Amerika novel. Method of collecting data used libraries techniques. Method of data analyzed used reading semiotic model that consist of heuristic and hermenuitic reading. There are three results of this study: (1) forming elements of novel: theme, character, flow, setting, (2) the religiouus values in the Bulan Terbelah di Langit Amerika novel by Hanum Salsabiela Rais dan Rangga Almahendra comprise faith, syariah (worship and muamalah), and morals. Implementation of research result from contained in novel BulanTerbelah di LangitAmerikaas materials criterian teach in high school. Keywords: BulanTerbelah di Langit Amerika novel, the semiotica, and implementation of the materials literarture in high school.